2002
DOI: 10.1177/0258042x0202700405
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Employee Relations Climate in Public Sector Undertakings

Abstract: Employee relations are the medium through which both employees and the company mutually co-operate for the maximum satisfaction of the economic, social and psychological wants ofall people. The objectives of the study are: (1) to analyse the employee relations climate existing at various levels and (2) to identify the various employee attitudes which determines the employee relations in an organised public sector company. It is concluded that Working conditions, Level of supervision, Communication, worker part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The results show that the climate is highly correlated with all components of effectiveness. Ganesan et al, (2002), studied the 'Determinants of Employee Relations Climate in Public Sector Undertakings.' The study revealed that by improving factors like working conditions, level of supervision, communication and worker's participation etc.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The results show that the climate is highly correlated with all components of effectiveness. Ganesan et al, (2002), studied the 'Determinants of Employee Relations Climate in Public Sector Undertakings.' The study revealed that by improving factors like working conditions, level of supervision, communication and worker's participation etc.…”
Section: Review Of Literaturementioning
confidence: 99%